1998
DOI: 10.1152/jn.1998.80.5.2699
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI of Galvanic Vestibular Stimulation

Abstract: The cortical processing of vestibular information is not hierarchically organized as the processing of signals in the visual and auditory modalities. Anatomic and electrophysiological studies in the monkey revealed the existence of multiple interconnected areas in which vestibular signals converge with visual and/or somatosensory inputs. Although recent functional imaging studies using caloric vestibular stimulation (CVS) suggest that vestibular signals in the human cerebral cortex may be similarly distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
215
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(248 citation statements)
references
References 57 publications
26
215
0
3
Order By: Relevance
“…A similar decrease in performance due to vestibular-spatial interaction eVects has been found in other studies that used vestibular stimulation in combination with speciWc cognitive tasks Mars et al 2005). Brain imaging studies suggest that areas in the posterior parietal cortex involved in mental transformation (Kosslyn et al 1998;Zacks et al 1999) are also activated during GVS-induced illusory body motion (Lobel et al 1998;Stephan et al 2005). Therefore, GVS activation of these areas presumably interferes and impairs mental transformation, corroborating Wndings of Mast et al (2006) who showed that caloric vestibular stimulation had a disruptive eVect on mental transformation but not on a cognitive control task not involving spatial imagery.…”
Section: General Inxuence Of Galvanic Vestibular Stimulation Versus Ssupporting
confidence: 75%
“…A similar decrease in performance due to vestibular-spatial interaction eVects has been found in other studies that used vestibular stimulation in combination with speciWc cognitive tasks Mars et al 2005). Brain imaging studies suggest that areas in the posterior parietal cortex involved in mental transformation (Kosslyn et al 1998;Zacks et al 1999) are also activated during GVS-induced illusory body motion (Lobel et al 1998;Stephan et al 2005). Therefore, GVS activation of these areas presumably interferes and impairs mental transformation, corroborating Wndings of Mast et al (2006) who showed that caloric vestibular stimulation had a disruptive eVect on mental transformation but not on a cognitive control task not involving spatial imagery.…”
Section: General Inxuence Of Galvanic Vestibular Stimulation Versus Ssupporting
confidence: 75%
“…We speculate that anosognosia stems, at least in part (Orfei et al, 2007;Aimola Davies et al, 2009), from damage to a region of the brain that integrates undesirable information, and that vestibular stimulation abolishes anosognosia by restoring or augmenting this specific processing function. Converging evidence from lesion studies of anosognosia (Berti et al, 2005) and from fMRI investigations of unrealistic optimism and vestibular stimulation (Lobel et al, 1998;Fasold et al, 2002) implicates the pars opercularis in right IFG as the region in question. In putting forward this suggestion, we emphasise some limitations of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Signals from the vestibular nuclei also project via the thalamus to (predominately contralateral) cortical and subcortical structures (Miller & Ngo, 2007). Notably, fMRI investigations have found that the cortical network activated during vestibular stimulation includes the pars opercularis region in the IFG (Lobel et al, 1998;Fasold et al, 2002). Remarkably, a number of studies have found that patients who previously have denied their left-sided hemisyndrome will transiently acknowledge it after left-ear irrigation with cold water (Cappa et al, 1987;Rode et al, 1992;Ramachandran, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…These are vestibular processing, multisensory integration as well as the perception of human bodies or body parts. The core region of the human vestibular cortex 25,26 is situated at the temporo-parietal junction including the posterior insula, and brain damage in this area has been associated with vestibular sensations and dysfunctions. 27,28 Several neuropsychological and neuroimaging studies suggest the implication of the temporo-parietal junction and cortical areas along the intraparietal sulcus in combining tactile, proprioceptive and visual information in a coordinated reference frame.…”
Section: Neurocognitive Mechanisms Of Obesmentioning
confidence: 99%